Metal-Free Transamidation of Secondary Amides via Selective N-C Cleavage under Mild Conditions - Liu, Yongmei; Shi, Shicheng; Achtenhagen, Marcel; Liu, Ruzhang; Szostak, Michal (Organic letters, 2017)
Nonplanar, electronically destabilized amides have emerged as powerful intermediates in organic synthesis. We report a highly selective method for transamidation of common secondary amides under mild, metal-free conditions that relies on transient N-selective functionalization to weaken amidic resonance. The combination of rational modification of the amide bond with nucleophilic addition mechanism, and the thermodynamic collapse of the resultant tetrahedral intermediate constitutes a two-step procedure to accomplish a challenging transamidation of secondary amides under mild conditions.